Breast cancer‐derived transforming growth factor‐β and tumor necrosis factor‐α compromise interferon‐α production by tumor‐associated plasmacytoid dendritic cells. Issue 3 (8th March 2013) - Sisirak, Vanja; Vey, Nelly; Goutagny, Nadège; Renaudineau, Sarah; Malfroy, Marine; Thys, Sandra; Treilleux, Isabelle; Labidi‐Galy, Sana Intidhar; Bachelot, Thomas; Dezutter‐Dambuyant, Colette; Ménétrier‐Caux, Christine; Blay, Jean‐Yves; et al.
<x xml:space="preserve">Abstract</x> We previously reported that plasmacytoid dendritic cells (pDCs) infiltrating breast tumors are impaired for their interferon‐α (IFN‐α) production, resulting in local regulatory T cells amplification. We designed our study to decipher molecular mechanisms of such functional defect of tumor‐associated pDC (TApDC) in breast cancer. We demonstrate that besides IFN‐α, the production by Toll‐like receptor (TLR)‐activated healthy pDC of IFN‐β and TNF‐α but not IP‐10/CXCL10 nor MIP1‐α/CCL3 is impaired by the breast tumor environment. Importantly, we identified TGF‐β and TNF‐α as major soluble factors involved in TApDC functional alteration. Indeed, recombinant TGF‐β1 and TNF‐α synergistically blocked IFN‐α production of TLR‐activated pDC, and neutralization of TGF‐β and TNF‐α in tumor‐derived supernatants restored pDCs' IFN‐α production. The involvment of tumor‐derived TGF‐β was further confirmed in situ by the detection of phosphorylated Smad2 in the nuclei of TApDC in breast tumor tissues. Mechanisms of type I IFN inhibition did not involve TLR downregulation but the inhibition of IRF‐7 expression and nuclear translocation in pDC after their exposure to tumor‐derived supernatants or recombinant TGF‐β1 and TNF‐α. Our findings indicate that targeting TApDC to restore their IFN‐α production might be an achievable strategy to induce antitumor immunity in breast cancer by combining TLR7/9‐based immunotherapy with TGF‐β and TNF‐α antagonists.